New Paradigms in Access to Scientific Information and the Role of the Internet Bilimsel Bilgiye Erişimde Yeni Paradigmalar ve Internetin Rolü - Bülent Karasözen (Türk Kütüphaneciliği, 1996)
TheThe Internet transforms the scholarly communication world-wide. Electronic preprint archives, electronic journals, discussion groups are some of the new ways to get access to information. This paper discusses some of these new developments from the perspective of scholarly communication. Among the topics covered are quality control of scientific publications in the electronic world, information overload, the impact of electronic publishing on libraries and publishers, and the economics of electronic publishing. Internet bilimsel bilgiye erişim açısından birçok yeni olanaklar sağlamaktadır. Elektronik önbası (preprint) arşivleri, elektronik dergiler, tartışma grupları Internet'in akademik dünyaya sağladığı olanaklardan sadece birkaçıdır. Bu makalede Internet'in özellikle akademik dünyaya etkisi, elektronik yayınlarda kalite kontrolü, aşırı bilgi yüklenmesi, elektronik yayıncılığın kütüphanelere ve yayıncılık sektörüne etkisi, elektronik dergilerin ekonomisi gibi konular tartışılmaktadır.